Myosin 7 and its adaptors link cadherins to actin - I-Mei Yu (Nature Portfolio, 2017)
Cadherin is essential for mechanotransduction and myosin-adaptor-harmonin complexes anchor it to actin. Here the authors present the structures of myosin 7 MF2 domains bound to the harmonin PDZ3c domain and give insights into myosin-adaptor-harmonin complex assembly.